Prevalence and correlates of early-onset menopause among women living with HIV in Canada. Issue 1 (January 2020) - Andany, Nisha; Kaida, Angela; de Pokomandy, Alexandra; Yudin, Mark H.; Wang, Lu; Kennedy, V. Logan; Webster, Kath; Loutfy, Mona
Abstract: Objective: Menopause is a pivotal transition for women. Previous studies have suggested increased risk of early menopause (40-45 years) and premature menopause (<40 years) for women with HIV. We aimed to determine age of menopause, prevalence of early menopause and premature menopause, and risk factors for menopause <45 years in Canadian women with HIV. Methods: This was a cross-sectional analysis from the Canadian HIV Women's Sexual and Reproductive Health Cohort Study. Analyses were restricted to biologically female participants reporting being postmenopausal (regardless of etiology). Primary outcome was median age at menopause. Predetermined variables, and those with P < 0.10 in univariable analyses were considered for inclusion into multivariable logistic regression model, to determine independent correlates of menopause <45 years. Results: 229 women were included. Median age of menopause was 48 years (interquartile range 43, 51); 29.7% of women experienced menopause <45 years: 16.6% with early menopause and 13.1% with premature menopause. In univariable analyses, menopause <45 years was more likely ( P < 0.05) with birth in Canada, white ethnicity, less than high-school education, smoking, recreational drug use, and hepatitis C co-infection. In multivariable modeling, less than high-school education (adjusted odds ratio [aOR] 2.45, 95% confidence interval [CI] 1.22-4.93) and hepatitis C co-infection (aOR 1.90, 95% CI 1.04-3.50) were independently associated with menopause <45 years. Conclusions: In Canadian women with HIV, median age of menopause was 48 years; 3 years younger than the general population. Only lower education and hepatitis C co-infection were independently associated with menopause <45 years, highlighting importance of socioeconomic factors and comorbidities. These findings have implications for counseling and management of women with HIV.